Ekonomia jako fundament postępu technicznego - Kuropatwa, Alicja (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The paper shows the causes of technological progress. One of them is economy, whereby technical progress is possible. But economic systems are diverse and not all of them grant development of new technologies. It should be noted that new technologies may progress mostly in a free market economy institutional environment. Particularly development is strengthened by: private property, the possibility of economic calculation, the correct allocation of resources, free competition between businesses etc. Currently, we are witnessing a continuous technological race thanks to the capitalist system and, as long as we follow this path, we will make further development possible. Also every step toward socialism will inhibit technological progress.
Keywords: ekonomia; postęp techniczny; nowe technologie